An advanced hybrid method for the acoustic prediction. (October 2015) - Redonnet, S.; Cunha, G.
Highlights: An advanced hybrid method for computational acoustics is proposed. Acoustic propagation is simulated via the Perturbed Euler Equations. Acoustic generation and propagation stages are weakly-coupled through an interface. The method is optimized via innovative features (forcing, derivation, interpolation). The method is validated and illustrated via noise problems of increasing complexity. Abstract: The present article proposes an advanced methodology for numerically simulating complex noise problems. More precisely, we consider the so-called multi-stage acoustic hybrid approach, which principle is to couple sound generation and acoustic propagation stages. Under that approach, we propose an advanced hybrid method which acoustic propagation stage relies on Computational AeroAcoustics (CAA) techniques. To this end, first, an innovative weak-coupling technique is developed, which allows an implicit forcing of the CAA stage with a given source signal coming from an a priori evaluation, whether the latter evaluation is of analytical or computational nature. Then, thanks to additional innovative solutions, the resulting CAA-based hybrid approach is optimized so that it can be applied to realistic and complex acoustic problems in an easier and safer way. All these innovative features are then validated on the basis of an academic test case, before the resulting advanced CAA-based hybrid methodology is applied to two problems of flow-induced noise radiation. This demonstrates the ability of the here proposed method to address realistic problems, by offering to handle at the same time both acoustic generation and propagation phenomena, despite their intrinsic multiscale character.